Hematometra in a Patient without Previous Surgeries/Anomalies in a Resource Constraint Setting- A Case Report from Bangem District Hospital - Fobellah, Nkengafac N; Asahngwa, Constantine; Bongfen, Charlotte; Gobina, Ronald; Odette, Kibu; Ngwa, Wilfred; Foretia, Denis (Archives of Clinical and Biomedical Research, 2021)
Background: Hematometra is a disorder where the uterus collects and gets filled with menstrual blood. This is usually due to a blockage at the cervix. It can either be congenital or acquired. Hematometra usually presents after puberty as primary amenorrhea. These patients present with recurrent cramping pelvic pain, urinary frequency or retention and a pelvic mass. On palpation, the uterus feels firm and enlarged. The goal standard is the evacuation of these blood clots by dilation and curettage (D C)./p> Case presentation: This patient was a 39-year-old non-pregnant, G2P1001 female, who presented in October 2020 with complaints of pelvic pain and pelvic pressure for two months with associated amenorrhea. She had no history of previous surgeries or cervical anomalies. Dilatation and curettage did not work out for her and so a low midline incision was done to the uterus and blood from the uterus was evacuated and later dilators were used inwardly to dilate her cervix. Her postoperative recovery was good and menses resumed immediately the month after till date. Conclusion: Once diagnosed of hematometra, there is immediate is need to evacuate the blood clots. Cervical stenosis is the most common cause of hematometra in patients with no history of previous surgeries or anomalies.